2012
DOI: 10.1002/csr.1303
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Development and Assurance of Corporate Social Responsibility Reports Published by Ibex‐35 Companies

Abstract: Spain is the world's leading country as regards corporate social responsibility (CSR) reporting (KPMG, 2011). In addition, Spain is taking new initiatives with regard to environmental policy, sustainable development, and stakeholder engagement in accordance with Law 2/2011.This is why we choose Spain as the setting to analyze whether the determinants for external assurance posited by existing literature (industry, size, profitability, leverage) have an impact on the decision of companies to assure their CSR re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

33
184
6
11

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 156 publications
(234 citation statements)
references
References 44 publications
33
184
6
11
Order By: Relevance
“…We found a significant association between adoption of assurance and size (p < 0.05), with large companies and MNEs being less likely to assure their sustainability reports than SMEs. This finding differs from the general behaviour, which reflects that the likelihood that adopting assurance is higher for large companies [4,5,45,63,64,66]. We also found that adoption of assurance is significantly associated with the use of the sector supplement (p < 0.05), with companies using the financial services supplement more likely to adopt assurance.…”
Section: Resultscontrasting
confidence: 72%
See 2 more Smart Citations
“…We found a significant association between adoption of assurance and size (p < 0.05), with large companies and MNEs being less likely to assure their sustainability reports than SMEs. This finding differs from the general behaviour, which reflects that the likelihood that adopting assurance is higher for large companies [4,5,45,63,64,66]. We also found that adoption of assurance is significantly associated with the use of the sector supplement (p < 0.05), with companies using the financial services supplement more likely to adopt assurance.…”
Section: Resultscontrasting
confidence: 72%
“…In contrast, Castelo Branco et al [64] indicated that listed companies were less likely to assure their sustainability reports. In relation to the company size, several authors found that larger companies were more likely to adopt assurance (see, for example, [4,5,45,63,64,66]). On the contrary, Cho et al [65] did not find that size was associated with adoption of assurance.…”
Section: Sustainability Assurancementioning
confidence: 99%
See 1 more Smart Citation
“…In fact, there are industries with high environmental impacts, so called environmentally-sensitive industries, and industries have a high political visibility because they have greater proximity to consumers, investors or employees (FernandezFeijoo et al, 2012). Consequently, the companies of environmentally-sensitive industries disclose more CSR information and their reports are externally assured in more proportion than companies installed in other industries because they seek the acceptance of their activities from stakeholders (Brammer & Pavelin, 2008;Kolk & Perego, 2010;Moroney et al, 2012;Toppinen et al 2012;Sierra et al, 2013;Alonso-Almeida et al, 2014). Thus, Industry1 is a control variable that measures the percentage of GRI reports disclosed by the high-risk industries over the total GRI reports by country and year.…”
Section: Independent and Control Variablesmentioning
confidence: 99%
“…They have gradually published reports on their charity donations and their activities of reducing pollutants, wastes, carbon emissions and energy consumption. According to Sierra et al (2012) Hernandez (2015) argues that, among contractors, developers and suppliers, contractors have the best performance in sustainable operation and development. As defined by Perrini et al (2003), corporate sustainability refers to the ability of a company to sustain its operation for a very long period of time and this ability depends on good relationships between the company and its stakeholders.…”
Section: Csr Researchmentioning
confidence: 99%